2006
DOI: 10.1111/j.1469-7580.2006.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of articular cartilage: does trypsin treatment produce consistent results?

Abstract: It is common practice in laboratories to create models of degraded articular cartilage in vitro and use these to study the effects of degeneration on cartilage responses to external stimuli such as mechanical loading. However, there are inconsistencies in the reported action of trypsin, and there is no guide on the concentration of trypsin or the time to which a given sample can be treated so that a specific level of proteoglycan depletion is achieved. This paper argues that before any level of confidence can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
(70 reference statements)
3
39
0
Order By: Relevance
“…Kiviranta et al [5] established a semi-quantitative histochemical estimation of glycosaminoglycans by microspectrophotometry based on the stoichiometric staining of proteoglycans. Moody et al [7] and Afara et al [3] adapted this method for quantifying the proteoglycan content in Safranin-O stained samples of articular cartilage by processing the stained image with ImageJ software (Wayne Rasband, National Institute of Health, USA). Safranin-O stain was used in this study because it has been previously shown to be an excellent cationic dye for histochemical quantification of cartilage matrix proteoglycans, since the staining intensity curves show high linear correlation (r = 0.900-0.995) with the fixed charge density curves from the adjacent cartilage [4].…”
Section: Histochemistry Vs Image Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiviranta et al [5] established a semi-quantitative histochemical estimation of glycosaminoglycans by microspectrophotometry based on the stoichiometric staining of proteoglycans. Moody et al [7] and Afara et al [3] adapted this method for quantifying the proteoglycan content in Safranin-O stained samples of articular cartilage by processing the stained image with ImageJ software (Wayne Rasband, National Institute of Health, USA). Safranin-O stain was used in this study because it has been previously shown to be an excellent cationic dye for histochemical quantification of cartilage matrix proteoglycans, since the staining intensity curves show high linear correlation (r = 0.900-0.995) with the fixed charge density curves from the adjacent cartilage [4].…”
Section: Histochemistry Vs Image Processingmentioning
confidence: 99%
“…Recently, image analysis-based protocols have been suggested and are gaining increased usage in biomechanical experiments [3][4][5][6][7] since they only require a very small biopsy rather than destruction of the entire sample, enabling their capacity to support experiments where progressive degradation of cartilage specimens is required. In this paper we observe that while this image analysis methodology [7] can deliver benefits over and above the biochemical or assay-based methods, there still remains the necessity to establish its accuracy and relationship to the well-established and extensively tested protocols [4,5]. To this extent we propose to determine whether or not there is a relationship between the data from image analysis and a standard protein (proteoglycan) quantification method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols used for the constituent degradation is in accordance with the previous studies. 27,28,36 The 4 h Trypsin-PBS treatment and 44 h collagenase treatments are known to remove all the proteoglycans and significantly disrupt superficial collagen, respectively. The alcian-blue test (see Sec.…”
Section: à2mentioning
confidence: 99%
“…[24][25][26] In addition, artificial degradation through enzyme treatment is commonly used to model proteoglycan loss and superficial collagen damage. 8,27 The main advantage of the artificial degradation is that the level of damage to the tissue can be controlled through enzyme concentration, the type of enzyme used and duration of the exposure. 27,28 Hence, artificial degradation can also be used to understand the role of individual constituents on mechanical behavior of the tissue.…”
mentioning
confidence: 99%